Evidence review to support the development of a Wellbeing Economy strategy in Scotland - Gerry McCartney; Clementine Hill O'Connor; Sue Laughlin; Tony Robertson; Lukas Bunse; Matthew Crighton; Aileen McLeod; Phoebe Cochrane; Francis Stuart; Iain Black; Robert McMaster (Post-growth Economics Network (PEN), 2025)
The Scottish Government published its 10-year National Strategy for Economic Transformation (NSET) in 2022. The NSET set out an ambition to create a Wellbeing Economy, but NonGovernmental Organisations (NGOs) who advocate for a Wellbeing Economy and environmental sustainability were critical both of the contents of the NSET, and the process used to create it. This paper seeks to provide a review of evidence to better inform the future development of economic strategy in Scotland, and rebalance the advice the original NSET was based upon, such that it might have a better chance of realising a Wellbeing Economy in the future.
Keywords: 330